Prokaryotic cytoskeletons : filamentous protein polymers active in the cytoplasm of bacterial and archaeal cells - Löwe, Jan (Deputy Director); Amos, L. A. (Springer, 2017)
"This book describes the structures and functions of active protein filaments, found in bacteria and archaea, and now known to perform crucial roles in cell division and intra-cellular motility, as well as being essential for controlling cell shape and growth. These roles are possible because the cytoskeletal and cytomotive filaments provide long range order from small subunits. Studies of these filaments are therefore of central importance to understanding prokaryotic cell biology. The wide variation in subunit and polymer structure and its relationship with the range of functions also provide important insights into cell evolution, including the emergence of eukaryotic cells"--Publisher's description.
Keywords: Cytoskeleton.; Prokaryotes -- Physiology.; elektronické knihy; electronic books